Economic Globalization, Domestic Politics and Income Inequality in the Developed Countries: A Cross-National Analysis - Vincent A. Malher (Luxembourg Income Study (LIS), 2001)
During the last decade, few issues have generated as much debate among scholars, policy-makers and political activists as the relationship between economic globalization and domestic income inequality in the developed world. The central aim of this paper is to offer an empirical assessment of the impact of economic globalization on the distribution of income generated by the market and the ability and willingness of states to redistribute it. Three basic analyses will be conducted. The first and most extensive is an unbalanced pooled cross-sectional time-series analysis of the international and domestic sources of cross-national variance in income distribution and redistribution for various years between the early 1980s and the early 1990s. This analysis will employ measures of post-government disposable income, pre-government earnings and fiscal redistribution that have been calculated from household-level income surveys available from the Luxembourg Income Study (LIS), which provides by far the most comprehensive, detailed and accurate cross-national data on income inequality currently available. The second analysis will offer a full-scale pooled cross-sectional time-series analysis of less complete and comparable annual data from non-LIS sources on pre-government wage dispersion between 1970 and 1990. Finally, the paper will examine trends over an even longer period in the distribution of post-government income in a single country, the United States, for which reliable annual figures are available for the period from 1967 to 1996. Among the questions addressed in the paper are the following: Is integration into the world economy systematically related to domestic income inequality across countries or over time? Can any economic dislocation resulting from globalization be ameliorated by the redistributive activities of the state? Are there differences in the impact of the three main modes of international integration, trade, direct foreign investment and global financial flows? To what extent are income distribution and redistribution the product of essentially domestic political variables not directly associated with economic globalization?
Keywords: 330; Einkommensverteilung; Globalisierung; Einkommensumverteilung; Industrieländer